Adubação nitrogenada em genótipos de soja associada à inoculação em semeadura direta no Cerrado - De Lisboa Parente, Tiago [UNESP] (2015)
The practice of inoculation of soybean seeds, with bacteria that fix atmospheric nitrogen (N), is widely used without adoption of mineral fertilizers. However, there are still questions about the efficiency of the practice supply the demand of the nutrient for the cultivars current, more productive and nutritionally demanding. The objective of this study was to evaluate the effect of nitrogen mineral fertilization, associated with inoculation, in two soybean cultivars. The experiment was conducted at the in Selvíria, Mato Grosso do Sul state. The experimental design was randomized blocks in a 4 × 2 factorial scheme, with four nitrogen levels (0, 10, 20 and 40 kg ha-1) and two application times (seeding and early-flowering). Treatments were applied in two soybean cultivars (BMX Potência RR and BRS Valiosa RR), with four replicates. Productive and morphological components of culture were evaluated, as well as the N levels in tissues and nodulation. The use of N at seeding committed nodulation in the two soybean cultivars, and for the BRS Valuable RR cultivar, the application of N at early-flowering increased the productivity, however, not enough to indicate this practice.